STUDY OF FRAMBOIDAL PYRITE IN SUB BASIN OF SOUTH PALEMBANG CASE STUDY: TOWNSITE AREA AND WEST BANKO MINE PIT - Fansurna Susanca, Rahmat
Acid Mine Drainage (AMD) could be formed when at least 3 components are in place, namely 1) sulfide minerals as the source of sulfur or acid, 2) oxygen as the oxidizing element, 3) water as the washer of oxidation result (Gautama, 2012). In sedimentary basins, pyrite, as a mineral of sulfide groups, can be formed through sulfur reduction of groundwater that contains iron ions. The form of the pyrite that resulted from this reduction will commonly be in the form of framboidal and will be more reactive in generating acid rather than coarse-grained non framboidal pyrite (Caruccio, 1972). In this research, 34 samples of coals taken from drilling activities in Townsite area and West Banko Mine Pit 1-3 area were observed and analyzed through macroscopic and polarized microscopic in order to obtain initial identification of the occurrence and distribution of framboidal pyite. Further clarifications were conducted using EDS-SEM tests to have deepen understanding on characteristic of framboidal pyrite. The results were then correlated with the previous research of study on rock geochemical carried out by Rembah (2015) in the same case study area. Vertically, using coal seam C as a bottom marker, it was found that in interburden layer B-C, the formation of framboidal is still in the stage of aggregation and in the form of uniformity greigite microcrystals which is the final stage of the formation process before it becomes framboidal pyrite. Rock geochemical test in this interburden showing that the rocks in this layer are potentially acid forming (PAF). In interburden layer A2-B1, framboidal pyrite was found in the form of aggregates framboidal (cluster framboids). It has the highest occurrence and is potentially acid forming (PAF). In interburden layer A1-A2, no framboidal pyrite was found. According to rock geochemical test, the rock in this layer can be categorized as not potentially acid forming (NAF). In overburden A1, framboidal pyrite was found in the form of aggregates framboidal (cluster framboids) with fewer distributions and not potentially acid forming (NAF).